Exploring Symbiosis: a Critique of Anthropocentrism in Jack London’s The Call of the Wild - Joshi, Bhup Raj (Khwopa Journal, 2024)
This article explores the relationship between human beings and animals with the ecocritical lens. The objective of this paper is to bring the original relation between human and nonhuman beings into context by addressing the question that how is human identity and existence shaped by animals and how can the symbiotic bonding between them be established for sustainable existence of all? The critical and theoretical insights from Emmanunel Levinas’s ethical considerations of interest, Jacques Derrida’s idea of relative existence along with the issues of ecological-environmental justice and other philosophical, ethical - biological views of the scholars are special considerations of this research to critique human and nonhuman animal dichotomy to bring out the state of symbiosis. It finds a symbiotic relationship between the two species that leads the work to critiquing pervasive speciesism in human. The human and nonhuman beings appear in the contesting relation in the culture leading to the state of negation, exploitation, consumption and extinction. From wild to tamed, aquatic to terrestrial, small to big, powerful to powerless all nonhuman animals have to live defensive lives and humans always behave in offensive way against them. The discourse that human is endowed with prerogatives over the nonhumans is self-created. So, the rivalry between human and animal is a suicidal contest between culture and nature